AB0371 HYDROXYCHLOROQUINE AS VIEWED BY LUPUS PATIENTS – WHAT IMPACT FOR DOCTORS?. (2nd June 2020) - Cornet, A.; Osmani, Z.; Frankel, S.
Abstract : Background: Hydroxychloroquine (HCQ) is recommended for all patients with systemic lupus erythematosus (SLE) and is typically considered as having a good safety profile 1 . Yet, patient organisations observe that concerns about eye impact or "allergies to HCQ" are often raised on social media. This could contribute to the non-adherence, which varies from 3 to 76% in SLE patients depending on assessment method and drug 2 . Objectives: To understand if/how some patients' beliefs impact adherence to HCQ treatment. Methods: In May 2019, LUPUS EUROPE launched a 29 questions on-line survey in 13 languages including questions on HCQ adherence. 2938 responses were analysed. 67.8% (1990 patients) were current HCQ users, 17.8% had stopped using it, 8.1% never had HCQ (6.4% did not respond to this question). 1820 users reported their adherence level. 314 (17.3%) were classified as "low" adherence as they reported missing/forgetting HCQ "always" (1.8%), "more than twice a week" (5.2%) or "once a week" (10.3%) Results: The prescribed HCQ dose, kidney involvement or duration of treatment (beyond the 1 st year) were found to have no impact on low adherence. Similarly, the user belief that HCQ has significant side effects, without experiencing these, was not found to impact adherence (p=.74). The following factors were associated with better adherence: (p<.0001) - The belief that HCQ is "Very important" (12.9% "low") rather than "important" (22.1% "low") or "not important / useless" (33.1% "low"). - Taking many different medications (9.8% "low" for Patients indicating more than 7 medications vs 19.8% for those listing 3 or less) Childhood onset of the SLE was associated with a lower adherence (30.0% "low" vs. 17.4% for later onset SLE (p<.001) 658 patients (29.6%) reported having experienced side effects. 42.6% of them stopped taking HCQ (patient led 161, doctor led 110, unclear 9). Amongst those continuing HCQ despite experiencing side effects, the proportion of non adherent patients increased to 24.7%, compared to 15.2% in the group of patients that have not experienced side effects (p=.0001). The 232 patients who talked with their Doctor and felt listened to appear to adhere better (22.0% low adherence) than the 84 who did not feel heard (31.0% low adherence), but the significance is only directional (p=<0.15) 523 patients have used HCQ in the past. 206 (39.4%) consider the decision to stop HCQ as doctor initiated, 272 (52.0%) as patient initiated, and 36 (6.9%) as a joint decision. When stopping was patient initiated, 59.9% was due to experiencing a significant side effect attributed by the patient to HCQ, 6.7% due to concern of a potential side effect, 11.2% "tested" stopping and noticed no difference, 10.0% were not convinced that it worked, 8.2% felt their lupus was less active, 2.6% wanted to reduce pill consumption. (Side effects attributed to HCQ may relate to age, disease activity or other factors). Conclusion: Doctors can help HCQ adherence by boosting patient's confidence in the importance of HCQ. Better patient education may contribute to avoid up to 40% of patient initiated decision to stop HCQ treatment. References: [1]Fanouriakis A et al. 2019 update of the EULAR recommendations for the management of systemic lupus erythematosus. Ann Rheum Dis. 2019 Jun; 78(6): 736-745. [2]Costedoat N et al, Treatment adherence in systemic lupus erythematosus and rheumatoid arthritis: time to focus on this important issue, Rheumatology, Vol 57 (9), Sep 2018, 1507–1509. Disclosure of Interests: None declared